2020
DOI: 10.1017/pls.2020.20
|View full text |Cite
|
Sign up to set email alerts
|

Disgust and disgust-driven moral concerns predict support for restrictions on transgender bathroom access

Abstract: Many U.S. states have proposed policies that restrict bathroom access to an individual’s birth sex. These policies have had widespread effects on safety for transgender and gender-nonconforming people, as well as on state economies. In this registered report, we assessed the role of disgust in support for policies that restrict transgender bathroom access. We found that sensitivity to pathogen disgust was positively associated with support for bathroom restrictions; sexual and injury disgust were unrelated. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This insight has proven valuable in explaining a variety of political attitudes. For example, people who are higher in disgust sensitivity are more likely to oppose interracial dating and marriage (Kam & Estes, 2016), hold more negative attitudes toward transgender people (Miller et al, 2017; Vanaman & Chapman, 2020), and worry about genetically modified foods and vaccines (Clay, 2017; Clifford & Wendell, 2016). Some of the clearest findings come from studies on homelessness.…”
Section: Disgust and The Behavioral Immune Systemmentioning
confidence: 99%
“…This insight has proven valuable in explaining a variety of political attitudes. For example, people who are higher in disgust sensitivity are more likely to oppose interracial dating and marriage (Kam & Estes, 2016), hold more negative attitudes toward transgender people (Miller et al, 2017; Vanaman & Chapman, 2020), and worry about genetically modified foods and vaccines (Clay, 2017; Clifford & Wendell, 2016). Some of the clearest findings come from studies on homelessness.…”
Section: Disgust and The Behavioral Immune Systemmentioning
confidence: 99%
“…On this view, sexual disgust–morality effects should be explained by the fact that sexual disgust increases perceptions of harm—that is, perceived harm is the causal mediator of the effects of sexual disgust on moral judgment. Although some work suggests that the effects of pathogen disgust on morality are mediated by harm (Schein et al, 2016), other work casts doubt on the ubiquity of such effects (Vanaman & Chapman, 2020). We are agnostic about the possibility of harm mediating the effects of sexual disgust on binding morality (though this model would seem at odds with the current finding that measures of sexual disgust were unrelated to the harm moral domain).…”
Section: Discussionmentioning
confidence: 99%
“…van Leeuwen et al, 2021 In 31 countries, disgust sensitivity was associated with greater negativity towards gay men and lesbians, but also to other groups associated with violations of traditional sexual norms. Vanaman and Chapman, 2020 Disgust sensitivity was associated with greater support for policies restricting public bathroom access for transgender people. Wilks et al, 2019 Disgust sensitivity was associated with opposition to lab-grown meat.…”
Section: Relationships Between Disgust Sensitivity and Social Judgmentsmentioning
confidence: 99%
“…There is evidence that this relationship extends to other sexual minorities including transgender men and women. For instance, Vanaman and Chapman (2020) found that greater disgust sensitivity (as measured by the pathogen subscale of the TDDS) was associated with greater support for requiring people to use public bathrooms that match their birth sex (that is, requiring transgender men and women to use bathrooms that do not match their felt/expressed gender identity). Indeed, disgust sensitivity seems to be broadly related to evaluations of groups associated with sex.…”
Section: Sexual Minoritiesmentioning
confidence: 99%